2015
DOI: 10.5505/agri.2015.27879
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound guided chronic pain interventions (Part I)

Abstract: SummaryRecently, ultrasonography (US) is an indispensible imaging technique in regional anesthesia practice. With the guidance of US, various invasive interventions in chronic pain pathologies of the musculoskeletal system, peripheral and neuroaxial pathologies has become possible. The management includes diagnostic blocks as weel as radiofrequency ablation and institution of neurolythic agents. During these algologic interventions we are able to see the target tissue, the dispersion of the drug and all nearby… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…fluoroscopy- or US-guided CESI [ 4 , 10 , 14 , 18 , 23 , 30 ]. Each of these studies reported different results on the advantages or disadvantages of each technique in terms of technical considerations, complications, and financial aspects [ 4 , 5 , 31 34 ]. The discrepancies between these studies might be attributed to methodological heterogeneities [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…fluoroscopy- or US-guided CESI [ 4 , 10 , 14 , 18 , 23 , 30 ]. Each of these studies reported different results on the advantages or disadvantages of each technique in terms of technical considerations, complications, and financial aspects [ 4 , 5 , 31 34 ]. The discrepancies between these studies might be attributed to methodological heterogeneities [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, conventional RF is routinely guided by X-rays, so it may increase the risk of radiation exposure to the patients and health care providers [ 12 ]. Thus, musculoskeletal ultrasonography has become a potential guidance method for RF instead of fluoroscopy in chronic pain management due to its unique advantages [ 13 , 14 ]. For example, ultrasound guidance is very accurate in peripheral or paraspinal nerve blocks to avoid injury of blood vessels and pleura [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%